Perancangan Desain Antarmuka Website dan Basis Data Tabungan Wadiah Pada Baitul Maal Wat Tamwil Nurul Iman - Krishnasari, Erneza Dewi; Soleha, Septiani; Fairuz, Zhavira Rifda (JISA(Jurnal Informatika dan Sains), 2019)
Baitul Mall Wat Tamwil (BMT) Nurul Iman is a non-governmental organization that manages savings, zakat, infaq and sodaqoh for community welfare. When serving savings of wadiah BMT Nurul Iman still using records manually with Microsoft Office Excel. There are complaints from customers, waiting time too long for finding customer data and t data needed by other divisions to be not integrated so that it requires extra time in the distribution of the data. Each one solution to overcome that problem is by developing applications to simplify the process of savings transactions, but currently there is no IT staff available at BMT Nurul Iman so that solutions for making the applications cannot be realized. This study an application design will be carried out for the savings transaction process on BMT Nurul Iman based on the website. The results of this study are website display designs based on usecase diagram and databases based on entitiy relationship diagram .